Evolution of defective structure of the irradiated silicon during natural ageing - Fodchuk, I.M.; Gutsulyak, T.G.; Himchynsky, O.G.; Olijnich-Lysjuk, A.V.; Raransky, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The defective structure of silicon single crystals grown by Chochralski method (Cz-Si) before and after an irradiation by high-energy electrons and gamma beams (E ~ 18 MeV) have been studied by the X-rey acoustic resonance method (XAR) and the method of low-frequency internal friction (LFIF). It is shown the basic types of defects that created after irradiation, have the dislocation nature. But their stability is different. It is also shown that in Cz-Si at room temperature (more 10000 hours) the relaxation of radiation defects in the ageing process occurs on the background of disintegration of oxygen oversaturated solid solution in silicon accompanying with occurrence of essential internal tensions.